1997
DOI: 10.1073/pnas.94.9.4342
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ERF-1 as a member of the AP2 transcription factor family

Abstract: The ERF-1 transcription factor was previously shown to be involved in the regulation of estrogen receptor (ER) gene transcription in hormonally responsive breast and endometrial carcinomas. In this study we sought to identify the gene for ERF-1. ERF-1 activates ER gene transcription by binding to the imperfect palindrome CCCT-GCGGGG within the promoter of the ER gene. ERF-1 protein was purified from the ER-positive breast carcinoma cell line, MCF7, utilizing ion exchange and DNA affinity chromatography. Peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 18 publications
3
94
0
Order By: Relevance
“…Table 3, the differential level of expression observed by the Atlas assay has been confirmed for some other genes by semiquantitative RT-PCR; in particular, a decreased expression has been confirmed for Sky tyrosine kinase receptor (Ohashi et al, 1994) and Erf-1 transcription factor (McPherson et al, 1997). On the contrary, RAD21, a factor involved in DNA repair and apoptotic cell death (Pati et al, 2002), and the anonymous cDNA KIAA0022 (Nomura et al, 1994) resulted in upregulation (not shown).…”
Section: Expression Of Plzf-regulated Genesmentioning
confidence: 78%
“…Table 3, the differential level of expression observed by the Atlas assay has been confirmed for some other genes by semiquantitative RT-PCR; in particular, a decreased expression has been confirmed for Sky tyrosine kinase receptor (Ohashi et al, 1994) and Erf-1 transcription factor (McPherson et al, 1997). On the contrary, RAD21, a factor involved in DNA repair and apoptotic cell death (Pati et al, 2002), and the anonymous cDNA KIAA0022 (Nomura et al, 1994) resulted in upregulation (not shown).…”
Section: Expression Of Plzf-regulated Genesmentioning
confidence: 78%
“…6 The estrogen receptor gene had previously been shown to be controlled by AP-2. 17 These results, however, were questioned by a different study, which found AP-2 expression to be higher in normal breast epithelia than in invasive tumors, 18 confirming a previous study, which had suggested that AP-2 might represent a novel tumor-suppressor gene because AP-2alpha/beta inversely correlated with ErbB-2 in invasive breast carcinoma. 19 To our knowledge, none of the studies addressed the spatial expression patterns of the different AP-2 isoforms on either normal breast tissue or breast tumor specimens.…”
mentioning
confidence: 69%
“…Methylation outside of the consensus sequence for SP1 induced a significant decrease in SP1 binding, leading to a reduced target gene expression (Zhu et al, 2003). AP-2 regulates genes involved in various biological functions, including p21 WAF/CIP (Zeng et al, 1997), transforming growth factor-a (Wang et al, 1997), estrogen receptor (McPherson et al, 1997), and tyrosine kinase receptor gene c-KIT (Huang et al, 1998). AP-2 also negatively regulates a number of genes, including c-myc (Gaubatz et al, 1995) and c-/EBP-a (Jiang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%